2014
DOI: 10.3329/bjvm.v12i1.20460
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gastrointestinal Parasites of Deer at Char Kukri Mukri in Bhola District

Abstract: To study the prevalence of gastrointestinal parasites of deer, 127 fecal samples were collected from Char Kukri Mukri upazilla of Bhola district of Bangladesh during the period from January to May, 2013. Eighty eight samples were found to be infected with gastrointestinal parasites and overall prevalence rate was 69.29%. Fasciola sp. (8.66%), Paramphistomum sp. (20.47%), stomach worm (18.11%), hook worm (20.47%), Strongyloides sp. (1.57%), Oesophagostomum sp. (1.57%), Eimeria sp. (6.30%) and Balantidium coli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The highest prevalence in rainy season might be due to more suitable environmental conditions in terms of humidity and temperature for the development of pre-parasitic stages of most of parasitic nematodes, whereas cold and dry climate have destructive effects on the development of the helminthic stages and allow fewer pre infective larvae to reach the infective stage (Soulsby, 1982). On the other hand, subsequent occurrence of gastrointestinal helminth infections was observed in summer (78.26%) followed by winter season (57.42%) during the present study which showed consistency with the observation of Kumar et al (2009), Sahoo et al (2009), Prevalence of Gastrointestinal Helminthic Infections in Black Bucks (Antilope cervicapra) of Tal Chhapar Sanctuary of Rajasthan Mahali et al (2010) in various states of India and Barmon et al (2014) from Bangladesh. This study revealed that heavy rainfall and high relative humidity predisposed the animals to heavy nematode infection.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The highest prevalence in rainy season might be due to more suitable environmental conditions in terms of humidity and temperature for the development of pre-parasitic stages of most of parasitic nematodes, whereas cold and dry climate have destructive effects on the development of the helminthic stages and allow fewer pre infective larvae to reach the infective stage (Soulsby, 1982). On the other hand, subsequent occurrence of gastrointestinal helminth infections was observed in summer (78.26%) followed by winter season (57.42%) during the present study which showed consistency with the observation of Kumar et al (2009), Sahoo et al (2009), Prevalence of Gastrointestinal Helminthic Infections in Black Bucks (Antilope cervicapra) of Tal Chhapar Sanctuary of Rajasthan Mahali et al (2010) in various states of India and Barmon et al (2014) from Bangladesh. This study revealed that heavy rainfall and high relative humidity predisposed the animals to heavy nematode infection.…”
Section: Resultssupporting
confidence: 91%
“…The overall prevalence for gastrointestinal helminths in the Blackbucks was recorded 72.46% during current study which is in compliance to the reports from many other Indian states of Punjab (Mir et al, 2016) and Odisha (Das et al, 2018) and from around the world including Latvia (Ruta et al, 2009) and Bangladesh (Barmon et al, 2014;Rahman et al, 2014). The high prevalence may be due to favorable climatic conditions, constant exposure of infestation and availability of infective stage larvae on the grazing ground by animals (Lama et al, 2015;Opara et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…However, the season wise prevalence was observed to be comparatively lower than the findings of Sahoo et al, (2009) who have reported prevalence of 47.62% in captive wild animals of Nandankanan Zoological Park, Bhubaneswar, Orissa. Barmon et al, (2014) have also reported a higher prevalence rate of gastro-intestinal parasites in summer (70.59%) and winter (66.67%) in wild animals of Char Kukri Mukri Upzilla of Bhola district of Bangladesh.…”
Section: Seasonal Prevalencementioning
confidence: 92%
“…Mesenteric veins and gall bladder were examined for the presence of flukes. Gastrointestinal tracts were examined for the detection of tapeworm and nematodes [14]. Fecal content was preserved in 10% buffered neutral formalin, shifted to the Department of Pathology, BAU for the detection of parasitic ova and protozoa (50ül/smear) by direct smear techniques [24].…”
Section: Parasitological Examinationmentioning
confidence: 99%
“…Due to the existence of a wildlife reservoir of M. bovis infection, primarily the Australian brushtail possum, eradicating TB from cattle and farmed deer in New Zealand has proven difficult [13]. The prevalence of gastrointestinal helminthiasis in deer in captivity and wildlife is frequent observation [14,15]. Data are lacking concerning the spectrum of infectious diseases present in deer either in captivity or wild conditions in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%